Analisis Dampak Program Bantuan Presiden Produktif Usaha Mikro (BPUM) Dalam Keberlangsungan UMKM di Kota Banjarmasin - Ramadhina, Aura; Fahrati, Eny (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study has the following objectives: Knowing the impact of the Productive Presidential Assistance for Micro Enterprises (BPUM) program on MSMEs in Kuin Cerucuk Village, West Banjarmasin District, and Knowing the effectiveness of the Productive Presidential Assistance for Micro Enterprises (BPUM) funds in the sustainability of MSMEs in Indonesia. Kuin Cerucuk Village, West Banjarmasin District. In this research, the writer uses a quantitative method through a descriptive approach. The primary data was typetained using questionnaires, interviews, and observations—technical analysis using descriptive analysis. The results of this study explain that BPUM funds positively impact MSMEs in Kuin Cerucuk Village, West Banjarmasin District. Assistance funds are allocated for business continuity during the COVID-19 pandemic and are used to meet household needs.